Perioperative Outcome of Carotid Endarterectomy with Regional Anesthesia (Medical Forum Monthly, 2022)
Objective: To assess the effect of regional anesthesia in patients treated with carotid endarterectomy.Study Design: A retrospective studyPlace and Duration of Study: This study was conducted at the surgical ward of Doctors Hospital & Medical Centre Lahore from August 2018 to August 2021 for a period of 03 years.Materials and Methods: A total of 150 patients undergoing carotid endarterectomy were included in the study and data was collected. Patients were administered with combined deep and superficial cervical plexus block. Remifentanil (0.025-0.05 mg/kg/min) was given to the patients during the procedure to make them comfortable, responsive and ensure their corporation. General anesthesia was only administered if the patient refused to consent to regional anesthesia or in case of any other complications. The main goal of the study was the occurrence of conversion from regional to general anesthesia during surgery.Results: Out of 150 patients, regional anesthesia was opted for 148 patients, while 2 patients were administered general anesthesia. In 1 patient, conversion from regional to general anesthesia took place as the patient was irritated. A shunt was introduced in 20 (13.3%) patients due to loss of consciousness of patients during the carotid clamping. Complications occurred in 1 patient (0.6%) due to neurological deterioration and 1 intraoperative acute myocardial infarction (0.6%). No intra-operative death occurred. 1 patient (0.6%) died during his hospital stay. 2 patients (1.3%) suffered a major stroke and 1 patient (0.6%) suffered a minor stroke. The total rate of stroke and death was 2.6% (4 patients).Conclusion: The in-hospital mortality under regional anesthesia in patients undergoing carotid endarterectomy is very low and requires very little conversion to general anesthesia. Hence regional anesthesia is regarded safe during carotid endarterectomy.